Knowledge improvement among participants of science research camp for secondary schools / Syamsul Herman, Suryani Ali and Noor Azlin Yahya - Herman, Syamsul; Ali, Suryani; Yahya, Noor Azlin (2002)
FRIM has been the venue chosen by the Ministry of Education for the National Science Research Camp since the year 2000. This camp is tailored for form four science stream students with the aim to expose them on research activities and to develop their interest in scientific careers. During the camps the students learned about the research conducted in FRIM and conducted experiments supervised by FRIM's research officers. Forty-nine students were asked to fill questionnaires before and after the six-day programme of the camp. In the questionnaire used in the pre-post evaluation, respondents were asked to define technical forestry terms used in forestry research. A scoring system with a maximum total of 50.00 points for all the fields of forestry research was developed to measure the level of knowledge among the respondents. The result showed that a maximum score was 11 points before participation and 21 points after participation. The lower points on the pre-evaluation suggested that most students have little background on forestry technical terms, where majority (20.41%) of the respondents scored only 1 point. An increase on the score was found for the post evaluation, where the majority of the respondents scored 9 (12.24%). Obviously, it showed an improvement on the knowledge level among the respondents. Different patterns of increment in knowledge level were also discovered in both male and female students. Pre-evaluation showed that female respondents scored as low as 2.74 points with the males scoring 3.27 points. However, post-evaluation resulted in distinct increment in the female respondents' level of knowledge (10.42) as compared to the males' (7.00). It showed an improvement of 7.68 points in the females '. Generally for all students, the average score for before and after the programme was 3.06 points and 8.33 points respectively, with 63.24% improvement in the level of score-point gained. From the study, it can be inferred that the students acquired a greater than two-fold improvement on their level of knowledge in science, especially in the area of forestry research, after their participation in the programme.